Sustainable food development for societies in hot arid regions: Thermoeconomic assessment of passive-cooled soil-based and hydroponic greenhouses - Omer Abedrabboh (17346847) (2023)
The intense growth in population in hot arid regions and heavy dependence on food imports resulted in many societies becoming food insecure. Moreover, heat waves and increasing average ambient temperatures have significantly increased plants' dehydration and death. Hot arid regions already experience very high ambient temperature levels and solar radiation, and the lack of freshwater resources, making cultivation expensive, energy-intensive, and vulnerable, if not impossible. Therefore, this study investigates the thermoeconomic performance of four different passive-cooled greenhouse configurations simulated for three large metropolitan areas (Doha, Cairo, and Karachi) located in different hot arid climates to analyze the possibilities and prospects for sustainable food production within the proximity of hot arid regions. First, a thermal performance assessment of the passive-cooled greenhouse combinations is performed for a typical day in every month of the year. Second, the evapotranspiration rate of the passive-cooled greenhouses is calculated to obtain water requirements. Third, a detailed economic analysis is executed for the different cultivation methods (soil-based and hydroponic). Fourth, an economic sensitivity analysis of the major input variables was studied to assess the greenhouses' economic robustness. Finally, the reduced environmental impact in (kg carbon dioxide eq.) of utilizing greenhouse passive cooling combinations relative to active cooling energy consumption is computed. Passive cooling combinations efficiently reduce high inside temperature by 2–6 °C, lower water requirements by 19–46%, and present an overall better economic and environmental performance. Other Information Published in: Journal of Cleaner Production License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jclepro.2023.137250